Choices : inside the making of India's foreign policy - Menon, Shivshankar, 1949- (Geopolitics in the 21st century., 2016)
A look behind the scenes of some of India's most critical foreign policy decisions by the country's former foreign secretary and national security adviser. Every country must make choices about foreign policy and national security. Sometimes those choices turn out to have been correct, other times not. In this insider's account, Shivshankar Menon describes some of the most crucial decisions India has faced during his long career in government#x97;and how key personalities often had to make choices based on incomplete information under the pressure of fast-moving events. Menon either participated d.